Endoscopic endonasal surgery for non-invasive pituitary neuroendocrinology tumors with incomplete pseudocapsule - Zhang, Gang; Wang, Pan; Wang, Junwei; Zou, Dewei; Yao, Hui; Liu, Jie; Tang, Chao; Jiang, Haotian; Tan, Xiaorong; Wu, Nan (Frontiers in Neurology, 2023)
Background: The pituitary neuroendocrinology tumors (PitNETs) with pseudocapsule can be effectively removed by the pseudocapsule-based extracapsular resection technique. In the areas without pseudocapsule, the tumor cells can spread into the adjacent tissues at the cellular level, which brings a great challenge to achieving total tumor resection. Methods: Our surgical strategy for PitNETs with an incomplete pseudocapsule is to combine the pseudocapsule-based extracapsular resection technique with the intensive excision technique for the removal of the tumor. Specifically, the pseudocapsule-based extracapsular resection technique is applied in the areas with pseudocapsule, while in the areas without pseudocapsule the intensive excision technique bounded by adjacent normal structures is adopted. Moreover, a pathological examination was performed to determine the situations of pseudocapsule and tumor cells remnant. Results: All growth hormone secreting PitNETs achieved biochemical remission after surgery. There was no deterioration of pituitary functions postoperatively, and the preoperative hypopituitarism had improved in all patients postoperatively. Two cases suffered a transient diabetes insipidus. And intraoperative cerebrospinal fluid leakage was observed in two cases, but no postoperative cerebrospinal fluid leakage in all cases. There was no recurrence during the follow-up. The fragmental pseudocapsule and small tumor remnants were found in the majority of suspicious tissues by histological staining. Conclusion: The effectiveness and safety of the surgical strategy was preliminarily explored for removing PitNETs without incomplete pseudocapsules. In overview, the pseudocapsule-based extracapsular resection technique is applied in areas with pseudocapsule, while the intensive excision bounded by adjacent normal structures is adopted in other areas.